Influence of lockup provision on IPO initial returns: Evidence from an emerging market - Mohd Rashid, Rasidah; Abdul Rahim, Ruzita; Mohd Nor, Abu Hassan Shaari; Yong, Othman (2013)
A lockup agreement ensures that major shareholders retain a significant economic interest in the companies following the IPOs.Rationally, these insiders will not adhere to the lockup agreement unless the benefits of doing so can more than offset the costs.Therefore, in an environment characterized by high information asymmetry, a lockup agreement can be an effective mechanism to signal the quality of the firms.Our observation of Malaysian IPOs indicates that (I) insiders commit to lockup more of their shares than required; (2) the percentage of lockup is different across firms; (3) the imposition of lockup provisions is more stringent on issuers that are riskier. The present study examines whether the lockup ratio and lockup period affect initial returns using a sample of 384 IPOs listed on Bursa Malaysia from 2000 to 2012. Since lockup provisions are imposed more stringently on riskier firms, higher lockup ratios and longer lockup periods are argued to signal higher risk and are therefore likely to result in investors requiring higher initial returns.Overall, the present study finds that the lockup period is significantly positive in explaining IPO initial returns, while the lockup ratio is not significant.The findings provide new insight for testing the signaling content of a lockup provision, particularly in settings characterized by high information asymmetry.